A multi-criteria approach for sustainable mass customisation in the fashion supply chain. (1st January 2012) - De Felice, Fabio; Gnoni, Maria Grazia; Petrillo, Antonella
Mass customisation (MC) relates to the ability to provide customised products or services through flexible processes in high volumes and at reasonably low costs which are currently key variables for the fashion supply chain. Sustainability concepts – which usually refer to three pillars i.e., economic, environmental and social ones – are new paradigms in this industrial sector, i.e., sustainable mass customisation. The paper proposes a methodological approach for evaluating sustainability performances of a fashion supply chain. Firstly, key performance indicators (KPIs) have been evaluated in order to assess sustainability level of a typical fashion supply chain according to the three single dimensions. KPIs have been derived from social and environmental life cycle analysis (LCA) and the supply chain operations reference (SCOR) model. Then, a multi-criteria model has been developed based on analytical network process (ANP) aiming both to model interrelationships among KPIs and to prioritise them.